VOCATIONAL COLLEGE TEACHERS IN MALAYSIA: CONFIRMATORY FACTOR ANALYSISFOR JOB ATTITUDE - Mohamad Zaid Bin Mustafa, MohdNorazmi Bin Nordin, Abdul Rasid Bin Abdul Razzaq, Badaruddin bin Ibrahim (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
This study aimed to validate elements of job attitudes that influence organizational commitment among vocational college teachers in Malaysia. Job attitude is often seen as something that makes a teacher successful or u nsuccessful in carrying out his or her job at school. Negative job attitudes reflect that a teacher’s commitment to the school organization is not as expected. Previous studies have found that cognitive, affective and behavioral elements are strongly associated with job attitudes. Therefore, this quantitative study was conducted to confirm the elements related to job attitude among vocational college teachers. The questionnaire was administered to 264 vocational college teachers in Malaysia randomly. The data obtained were then analyzed using Structural Equation Modelling (SEM) using AMOS 21 software. Confirmatory Factor Analysis was performed to obtain factor loading for each element obtained namely cognitive, affective and behavior. The analysis results show that the factors reflect the appropriate fit and meet all the criteria for validation.